2018
DOI: 10.25135/acg.oc.38.18.02.067
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Theoretical Calculation and α-glucosidase inhibition of new chalcone oximes

Abstract: A series of eleven hydroxy and methoxy by the condensation of chalcone (1asynthesized compounds were characterized using NMR (1D; ROESY), FT-IR, UV, LC-MS spectral data and elemental analysis. These synthetic compounds ( screened for their α-glucosidase inhibition. Th compounds 2a and 2b with in the range of 1.61 (IC 50 , 13,34 µM). IC 50 values of other synthesized compounds which were more or as active as acarbose, but, IC geometric isomers of compounds 2a-2k showed that cisoid 1E,2E is the most stable geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…semicarbazone and thiosemicarbazone 3-phenylquinazoline-2,4(1H,3H)-dione active Schiff bases (Muleta & Desalegn, 2022;Soman & Jain, 2022), ferrocene Chalcone-based Schiff bases (Liu et al, 2018), 1,2,4-oxadiazole-chalcone/ oxime hybrids Schiff base hybrids (Ibrahim et al, 2021), hydrazinecarbothiamide and hydrazine-carboxamide Schiff base derivatives (Siddiqui et al, 2019) and deoxybenzoin Chalconebased Schiff base hybrids (Luo et al, 2012) with anticancer (Liu et al, 2018), antimicrobial (Aiwonegbe & Usifoh, 2021), antioxidant (Muleta & Desalegn, 2022), antidiabetic (Fandaklı et al, 2018), immunosuppressant (Luo et al, 2012) and tyrosine inhibitors (Radhakrishnan et al, 2016), were reported.…”
Section: Graph Theoretical Analysis Pharmacoinformatics and Molecular...mentioning
confidence: 99%
“…semicarbazone and thiosemicarbazone 3-phenylquinazoline-2,4(1H,3H)-dione active Schiff bases (Muleta & Desalegn, 2022;Soman & Jain, 2022), ferrocene Chalcone-based Schiff bases (Liu et al, 2018), 1,2,4-oxadiazole-chalcone/ oxime hybrids Schiff base hybrids (Ibrahim et al, 2021), hydrazinecarbothiamide and hydrazine-carboxamide Schiff base derivatives (Siddiqui et al, 2019) and deoxybenzoin Chalconebased Schiff base hybrids (Luo et al, 2012) with anticancer (Liu et al, 2018), antimicrobial (Aiwonegbe & Usifoh, 2021), antioxidant (Muleta & Desalegn, 2022), antidiabetic (Fandaklı et al, 2018), immunosuppressant (Luo et al, 2012) and tyrosine inhibitors (Radhakrishnan et al, 2016), were reported.…”
Section: Graph Theoretical Analysis Pharmacoinformatics and Molecular...mentioning
confidence: 99%
“…The antidiabetic activity of the synthesized ligands was determined by the α-Glucosidase inhibition assay against acarbose. Both of the compounds showed significant activity 10 and the structures of these compounds are given in figure 5. the status of the caspase 3 protein by using anti-cleaved caspase 3 antibodies.…”
Section: Chalcone-based Schiff Base Derivatives As Antidiabetic Agentsmentioning
confidence: 99%
“…The chalcones are also of great importance due to their various therapeutic applications and diverse applications. The Schiff bases based on chalcone derivatives such as pyrazole and 2-pyrazoline derivatives 7 , thiosemicarbazone derivatives and other derivatives exhibited various pharmacological activities like antimicrobial 8 , anticancer 9 , antidiabetic 10 and antioxidant activities 11 . These Schiff base linkages (azo or imine) enhance the sensing properties of the thermotropic liquid crystals, provides thermal stability and also the liquid crystalline properties of the compounds containing chalcone linkages are enhanced 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Fandaklı et al (2018) reported the α-glucosidase inhibitory activity of synthesized chalcone oximes (2a-2k). Amongst tested compounds, compounds 2a and 2b showed more effective activity against α-glucosidase with IC 50 values of 1.61 ± 0.16 µM and 3.36 ± 0.58 µM [ 26 ].…”
Section: Reviewmentioning
confidence: 99%